Birth and Health Outcomes of Children Migrating With Parents: A Systematic Review and Meta-Analysis - Chang, Ruixia; Li, Chunan; Qi, Haiqin; Zhang, Ya; Zhang, Jianduan (Frontiers in Pediatrics, 2022)
Objective To examine the birth and health outcomes of children migrating with parents internationally and domestically, and to identify whether the healthy migration effect exist in migrant children. Methods Five electronic databases were searched for cross-sectional, case-control, or cohort studies published from January 1, 2000 to October 20, 2020 and written by English language, reporting the risk of health outcomes of migrant children (e.g., birth outcome, nutrition, mental health, physical health, death, substance use and academic outcomes.) We excluded studies in which participants’ age more than 18 years, or participants were forced migration due to armed conflict or disasters, or when the comparators were not native-born residents. Pooled odd ratios (ORs) were calculated using random-effects models. Results Our research identified 10,404 records, of which 106 studies were retrained for analysis. The majority of the included studies (94, 89%) focused on international migration and 12 (11%) on migration within country (primarily China and India). Compared with native children, migrant children had increased risks of fetal death (OR 1.24 [95% CI 1.07-1.45]), perinatal death (OR 1.25 [95% CI 1.04-1.50]), neonatal death (OR 1.10 [95% CI 1.02-1.19]), under-five death (OR 1.24 [95% CI 1.16-1.34]), small for gestational age (OR 1.18 [95% CI 1.12-1.25]), overweight/obesity (OR 1.33 [95% CI 1.13-1.57]), iron-deficiency anaemia (OR 1.37 [95% CI 1.01-1.87]), depression (OR 1.29 [95% CI 1.00-1.65]), schizophrenia (OR 1.79 [95% CI 1.50-2.14]), suicide attempt (OR 1.31 [95% CI 1.10-1.56]), oral/eye diseases (OR 1.97 [95% CI 1.48-2.62]), and gastrointestinal diseases (OR 1.56 [95% CI 1.18-2.07]). However, the risks of low birth weight (OR 0.86 [95% CI 0.79-0.94]), preterm (OR 0.90 [95% CI 0.84-0.97]), and non-breastfeeding (OR 0.72 [95% CI 0.57-0.92]) were lower among migrant children as compared to non-migrant children. Study quality varied across the included studies, with 23% assessed as high or unclear risk of bias. Conclusions Migrant children had overall poorer health outcomes. No obvious evidence observed regarding healthy migration effect. Actions are required to address the health inequity among these populations.